Realisation of the double sweep method by using a Sleptsov net. Issue 6 (2nd November 2021) - Kostikov, Alexander A.; Zaitsev, Nikolay D.; Subotin, Oleg V.
Abstract : The present article is focused on the application of Sleptsov net (SN) for solving system of linear algebraic equations with a tridiagonal matrix. SN, which implements the double sweep algorithm for solving a system of linear equations with a tridiagonal matrix, is constructed. The work of the constructed network is considered when solving a specific example. The number of operations carried out by the net in performing computations has been calculated and the performance of the parallel double sweep method implemented by the net is compared with the sequential double sweep method. We also consider representation of integer and real numbers by a SN and implementation of basic arithmetic operations over these numbers because the implementation of the algorithm requires floating point operations. GRAPHICAL ABSTRACT: UF0001